Multi-omics profiling identifies berberine and salidroside as potential immunoregulatory compounds in radiation-induced skin injury - Zhu, Mengru; Shang, Yuxuan; Zhao, Mingjian; Liu, Jia; Wang, Fengya; Zou, Wei; Wang, Bing; Liu, Lukuan; Liu, Jing (Frontiers in Immunology, 2025)
BackgroundRadiation-induced skin injury is a significant concern in nuclear accidents and cancer radiotherapy (RT). Skin damage ranges from mild erythema to severe ulceration, which significantly affects the patients’ quality of life. While previous studies have highlighted the role of the apoptotic pathway, its precise mechanism in radiation-induced skin damage remains unclear.MethodFirst, single-cell RNA and RNA-seq datasets were searched using the Gene Expression Omnibus (GEO) database, and further subgroup analysis of fibroblast skin cells, pseudotime analysis, and cell-cell communication analysis were conducted to determine the important state during fibroblast differentiation. Next, we analyzed and screened the key genes in the RNA-seq data. Finally, we performed SA-β-gal staining, flow cytometry, and qRT-PCR in an in vitro irradiation model to validate TGFBR2 as a potential therapeutic target.ResultThe apoptotic pathway plays a crucial role in fibroblasts. Subsequent analysis of fibroblast subtypes revealed different subtypes, including MMP3, Coch, Apod, and Eif4e. Enrichment analysis further demonstrated a significant upregulation of apoptosis in MMP3 fibroblasts (FIB). Pseudotime analysis indicated that MMP3 FIB exhibited high stemness within the fibroblast differentiation trajectory, while intercellular communication analysis underscored the critical role of TGF-β in fibroblast subtype interactions. Additionally, RNA-Seq analysis identified TGFBR2 as a key gene. In vitro experiments corroborated the essential function of TGFBR2 in radiation-induced skin injury. Lastly, molecular docking studies identified potential therapeutic agents, including Berberine and Salidroside.ConclusionThis study integrates single-cell and bulk transcriptomic analyses to reveal apoptosis-sensitive fibroblast subtypes involved in radiation-induced skin injury. MMP3+ fibroblasts were identified as a key apoptotic population with high stemness potential, and TGFBR2 was validated as a central regulatory target through molecular and cellular assays. Furthermore, Berberine and Salidroside were identified via molecular docking as potential compounds targeting TGFBR2. These findings provide mechanistic insight into fibroblast heterogeneity under radiation stress and offer a foundation for targeted therapeutic strategies.